2018
DOI: 10.1136/bmjopen-2017-019050
|View full text |Cite
|
Sign up to set email alerts
|

Variations in outcomes by residential location for women with breast cancer: a systematic review

Abstract: ObjectivesTo systematically assess the evidence for variations in outcomes at each step along the breast cancer continuum of care for Australian women by residential location.DesignSystematic review.MethodsSystematic searches of peer-reviewed articles in English published from 1 January 1990 to 24 November 2017 using PubMed, EMBASE, CINAHL and Informit databases. Inclusion criteria were: population was adult female patients with breast cancer; Australian setting; outcome measure was survival, patient or tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 119 publications
0
24
0
Order By: Relevance
“…A modified (14) version of the Newcastle-Ottawa Scale (NOS) (15), a risk-of-bias assessment tool for nonrandomized studies, was used for quality assessment. Studies were scored according to the extent that they met each of the nine assessed criteria using an ordinal scale to rate the risk of bias as 0 (high), 1 (intermediate), and 2 (low).…”
Section: Critical Appraisalmentioning
confidence: 99%
“…A modified (14) version of the Newcastle-Ottawa Scale (NOS) (15), a risk-of-bias assessment tool for nonrandomized studies, was used for quality assessment. Studies were scored according to the extent that they met each of the nine assessed criteria using an ordinal scale to rate the risk of bias as 0 (high), 1 (intermediate), and 2 (low).…”
Section: Critical Appraisalmentioning
confidence: 99%
“…Previous reviews (Dasgupta et al, 2017(Dasgupta et al, ,2018Lyle et al, 2017;Tapia et al, 2017;Youl et al, 2016) focus on specific groups of women with breast cancer in Australia. To the knowledge of the review authors, this is the first review that takes a holistic approach to explore all the proposed factors cited in the literature that contribute to poorer breast cancer outcomes in Australia, including tumour characteristics, patient characteristics (Indigenous status, ethnic minority groups, place of residence, and socioeconomic status) and treatment characteristics.…”
Section: Strengths Of This Reviewmentioning
confidence: 99%
“…Two provided strong evidence that Indigenous women had poorer survival outcomes than non‐Indigenous women due to more extensive disease at diagnosis, delays in diagnosis and/or treatment, geographical isolation, higher comorbidity burden, socioeconomic disadvantage and limited access to surgical treatment (Dasgupta et al, ; Tapia et al, ). Another review demonstrated consistently poorer survival for geographically isolated women, attributing this largely to more advanced disease at diagnosis, treatment‐related factors and socioeconomic disadvantage (Dasgupta et al, ). These characteristics were reflected in another review which explored the psychosocial outcomes for women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several factors which lead to increased breast cancer incidence and cancer-related mortality. These can be classified into patients, tumour and treatment characteristics 83–85. These characteristics include patient age, ethnicity, tumour type, size, grade, stage, hormone receptor status, type of surgery and the use of adjuvant therapies 83–85.…”
Section: Discussionmentioning
confidence: 99%